IMPROVING STUDENTS’ MASTERY OF PASSIVE TROUGH EGRA METHOD - Dini Siti Sundari (University of Kuningan, 2016)
This research aims at finding out whether or not EGRA method can improve students’ mastery of passive voice in one of Public Senior High Schools in Kuningan. A quasi-experimental design was employed in this research to test the objective theories by examining the relationship between two variables. Pre-test, post-test, and questionnaire were used to collect the data. The data were then analyzed by using SPSS 20.0. Before conducting pre- and post-test, the tests were tried out to check its validity and reliability. From 60 items, it was found that 40 items were valid and reliable because the items’ correlation coefficient (rxy) were higher than rtable and their Cronbach Alpha were higher than 0.07, so the researcher used them as pretest and posttest instruments. The t-test result was 0.000 which means that it was lower than 0.05 (0.0000.05) so that the null hypothesis is rejected and alternative hypothesis is accepted. Then, the mean score of pre-test and post-test in experimental group were significantly different (55.77 up to 81.79). To confirm the result of this research, questionnaires were used. From the questionnaire, it was found that in affective aspects, 58.9%, 64.1% and 53.8% of the students agreed with the use of EGRA method. In behavioral aspects, 33.3%, 56.4% and 43.5% of the students agreed with the use of EGRA method. While in cognitive aspects, 56.4%, 56.4%, 51.2% and 58.9% of the students agreed with the use of EGRA method. So, it can be concluded that EGRA method can improve students’ mastery of passive voice.Keywords: EGRA method, passive voice, students